The solution to the given system of equation is (25/7, 6/7)
<h3>System of equation</h3>
Given the system of equation expressed as:
x= - 4y+7 ........... 1
-2y+3x=9 ...........2
Substitute the equation 1 into 2 into have:
-2y + 3(-4y+7) = 9
-2y + 3(-4y) + 3(7) = 9
-2y - 12y + 21 = 9
Collect the like terms
-14y = 9- 21
-14y = -12
y = 6/7
Substitute y = 6/7 into equation 1;
x =-4y + 7
x = -4(6/7) + 7
x= -24/7 + 7
x = -24+49/7
x = 25/7
Hence the solution to the given system of equation is (25/7, 6/7)
Learn more on system of equation here; brainly.com/question/14323743
#SPJ1
y² = 8y - 15 (alternate angles are equal)
y² - 8y + 15 = 0
(y - 5)(y - 3) = 0
y = 5 or 3
x + 8y - 15 = 180 (angles in a straight line add up to 180)
when y = 5
x + 40 - 15 = 180
x = 155°
when y = 3
x + 24 - 15 = 180
x = 171°
Step-by-step explanation:
step 1. let's assume they are drawn without replacement and probability is denoted P.
step 3. P = (5/17)(4/16)(3/15)
step 4. P = (5/17)(1/4)(1/5)
step 5. P = 5/340
step 6. P = 1/68 = 0.0147 = 1.5%
Answer:
335.5 in^2
Step-by-step explanation:
The area is a rectangle and a triangle
The area of the rectangle is
A = a*b where a is 11 and b is 25
A = 11*25 =275
The area of the triangle is
A = 1/2 b*h where b is 11 and h is 11
A = 1/2 (11) * 11
A = 60.5
The total area is 275+60.5=335.5
Answer:
no
Step-by-step explanation: